2019
DOI: 10.1093/jnci/djz037
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility of Early Breast Cancer Surveillance in Survivors of Thoracic Radiation-Treated Adolescent Hodgkin Lymphoma

Abstract: Background Adolescent women treated for Hodgkin lymphoma (HL) are at increased risk of breast cancer (BC). We evaluate the cost-utility of eight high-risk BC surveillance strategies for this population, including the Children’s Oncology Group guideline of same-day annual mammography and magnetic resonance imaging (MRI) beginning at age 25 years. Methods A discrete event simulation model was used to simulate the life histories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…To overcome these challenges, researchers have used simulation modeling to evaluate the clinical effectiveness and cost-effectiveness of endorsed strategies. 46,[49][50][51] Despite being limited in scope (radiation-related breast cancer, 46,52,53 colorectal cancer, 54 anthracycline-related cardiomyopathy [49][50][51] ), these efforts have facilitated the refinement and often the deintensification of recommended screening frequencies. 46,[49][50][51] Notably, they have paved the way for much-needed efforts to evaluate existing screening recommendations across a broader set of health outcomes and to assess multilevel interventions seeking to reduce the burden of morbidity in survivors.…”
Section: Rigor In Guideline Development and Evaluation Of Late Effects Screeningmentioning
confidence: 99%
“…To overcome these challenges, researchers have used simulation modeling to evaluate the clinical effectiveness and cost-effectiveness of endorsed strategies. 46,[49][50][51] Despite being limited in scope (radiation-related breast cancer, 46,52,53 colorectal cancer, 54 anthracycline-related cardiomyopathy [49][50][51] ), these efforts have facilitated the refinement and often the deintensification of recommended screening frequencies. 46,[49][50][51] Notably, they have paved the way for much-needed efforts to evaluate existing screening recommendations across a broader set of health outcomes and to assess multilevel interventions seeking to reduce the burden of morbidity in survivors.…”
Section: Rigor In Guideline Development and Evaluation Of Late Effects Screeningmentioning
confidence: 99%
“…While this population was highly specific, it still fell within the scope of this review. 21 Furzer et al found that annual mammography-based breast cancer screening beginning at age 25 was associated with an ICER of $43,000/QALY, while a switch to annual MRI starting at age 50 had an ICER of $148,000/QALY. 21 Lastly, screening using annual MRI starting from age 25 had an ICER of $227,222/QALY.…”
Section: Quality Assessment Study Quality Was Assessed Using the Cons...mentioning
confidence: 99%
“…21 Furzer et al found that annual mammography-based breast cancer screening beginning at age 25 was associated with an ICER of $43,000/QALY, while a switch to annual MRI starting at age 50 had an ICER of $148,000/QALY. 21 Lastly, screening using annual MRI starting from age 25 had an ICER of $227,222/QALY. 21 However, despite large differences in ICERs, the life expectancy between the various surveillance methods had very little variation, as it ranged from 45.73 years (for annual mammography starting at age 30 years) to 45.90 years for (annual mammography and MRI starting at age 25 years).…”
Section: Quality Assessment Study Quality Was Assessed Using the Cons...mentioning
confidence: 99%
“…Simulation, using Markov health states is currently being used to address cost-effectiveness of breast cancer screening recommendations. 143…”
Section: Screening Recommendations For Early Detection Of Subsequent Primary Neoplasms In Childhood Cancer Survivorsmentioning
confidence: 99%